Mathematics and science teachers’ sense of self-efficacy and English language proficiency / Zanariah Ridzwan - Ridzwan, Zanariah (2011)
The implementation of ETeMS (English in the Teaching of Mathematics and Science) in Malaysia in 2003 posed many challenges to both the students and teachers. One of the main issues is the lack of English language proficiency among the Mathematics and Science teachers. In 2009, the Education Minister announced the reversal in the policy and Mathematics and Science will again be taught in Bahasa Malaysia or vernacular languages by 2012. Many studies have been carried out linking teachers’ sense of selfefficacy to positive academic outcomes including English language proficiency. The main purpose of this study is to measure the level of teachers’ sense of self-efficacy, English language proficiency and to investigate if there is a significant relationship between the two variables. In this correlational descriptive study, 100 Mathematics and Science teachers from five secondary schools in the Petaling Utama district, Petaling Jaya, Selangor responded to the given questionnaires. A mixed method approach was used to analyze the data. The results showed that the teachers are fairly efficacious which means that they are confident of their teaching abilities and that these abilities will make a difference in student learning. The result also showed that the teachers are moderately to very proficient in the English language. Correlational analysis showed positive correlation between teacher efficacy and English language proficiency. The implications and recommendations of the study are also discussed.